Awareness Regarding Cervical Cancer among Reproductive Aged Women in Community of Sudurpaschim Province in Nepal - Ranabhat, Mina Kumari; Chand, Babita (Nepalese Journal of Cancer, 2025)
Background: Cervical cancer is the fourth most frequently diagnosed cancer and the fourth leading cause of cancer-related deaths among women worldwide. It is the second leading cancer in Nepali women. The objective of this study is to find out the awareness regarding cervical cancer among reproductive aged women of Sudurpaschim Province in Nepal. Methods: A cross sectional study was used among 100 reproductive aged women by using non-probability purposive sampling technique with semi-structured interview schedule. The data were analyzed in Statistical Package for the Social Science (SPSS) version 22 using descriptive and inferential statistics. Results: Out of 100 reproductive aged women 34% were belonged to the age group of 25-34 with means (30.35±9.324), minimum age was 15 and maximum age was 49 years. As well as educational status 39% had basic education and 11 % had no informal education. Similarly, all the reproductive aged women followed Hindu religion. Likewise, 83% reproductive aged women were married and 17% were unmarried. Regarding awareness of cervical cancer 69 % reproductive aged women had moderate, 24% had high and only 7% had low. Level of awareness regarding cervical cancer is statistically significant with the age of reproductive aged women (p=0.021), Ethnicity (p=0.05) and age of marriage (p=0.012). Conclusion: The finding of the study concluded that awareness regarding cervical cancer among reproductive aged women is moderate and most of the reproductive aged women were unaware about HPV vaccination and cervical cancer screening so cervical cancer screening awareness and education programs are needed to prevent cervical cancer.